Accurate thermal-induced structural failure analysis under incompressible conditions. (15th June 2022) - Moreira, Carlos A.; Barbat, Gabriel B.; Cervera, Miguel; Chiumenti, Michele
Abstract: In this work, the performance of the mixed 3-field displacement/deviatoric-strain/pressure ( u / e / p ) finite element is examined for nonlinear thermo-mechanical structural applications under incompressible behavior. The proposed FE model increases the solution accuracy in terms of strains and stresses, guaranteeing mesh-objective results in nonlinear analyses. Structural failure is modelled with J2-plasticity and J2-damage constitutive laws, introducing the isochoric behavior, typical of metals, in the material response. The solution of the coupled thermal and mechanical problems follows a staggered scheme and temperature dependent material properties are introduced to study the effect of the thermal coupling in the mechanical problem. This FE approach is applicable with any interpolation basis: triangles, quadrilaterals, tetrahedras, hexahedras and prisms. A set of numerical benchmark problems is proposed to examine the influence of the enhanced accuracy of the proposed model in thermally-induced structural failure analyses in incompressible conditions. The study includes the comparison of the u / e / p and u / p FE formulations, where the effect of the thermal coupling in the problem is investigated. The superior performance of the 3-field formulation with regard to the evaluation of collapse mechanisms, failure loads, mechanical dissipation and numerical stability in incompressible situations is shown. Highlights: Displacement/deviatoric-strain/pressure mixed finite element formulation. Thermo-mechanical coupling. Accurate thermal-induced failure analysis. FE technology suitable for incompressible materials.